A Chiral Metal—Organic Framework Prepared on Large-Scale for Sensitive and Enantioselective Fluorescence Recognition - Zhang, Xin-Mei; Bai, Yan-Mei; Ai, Lu-Lu; Wu, Fang-Hui; Shan, Wei-Long; Kang, Yan-Shang; Luo, Li; Chen, Kai; Xu, Fan (Molecules (Basel, Switzerland), 2023)
MOF-based luminescent sensors have garnered considerable attention due to their potential in recognition and discrimination with high sensitivity, selectivity, and fast response in the last decades. Herein, this work describes the bulk preparation of a novel luminescent homochiral MOF, namely, [Cd(s-L)](NO3)2 (MOF-1), from an enantiopure pyridyl-functionalized ligand with rigid binaphthol skeleton under mild synthetic condition. Except for the features of porosity and crystallinity, the MOF-1 has also been characterized with water-stability, luminescence, and homochirality. Most important, the MOF-1 exhibits highly sensitive molecular recognition toward the4-nitrobenzoic acid (NBC) and moderate enantioselective detection of proline, arginine, and 1-phenylethanol.